Perspektif Ontologi Islam dalam Pembentukan Karakter Siswa di SD Negeri 02 Karang - Mujiburrohman, Mujiburrohman; Widyaningsih, Erna (Darul Yasin Al Sys, 2025)
Islamic education is rooted in ontological principles that emphasize human existence as faithful and responsible beings. This study aims to analyze the Islamic ontological perspective in character building among students at SD Negeri 02 Karang. Islamic ontology, which focuses on the essence of existence and the relationship between humans and Allah SWT, serves as an essential foundation in the development of character values. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews with three respondents: two male teachers and one female teacher, along with photographic documentation of the interviews. The findings indicate that the implementation of Islamic ontological values, such as faith, sincerity, and responsibility, plays a significant role in shaping students' character. Teachers utilize an integrative teaching approach, connecting spiritual values with the school curriculum. This study concludes that understanding Islamic ontology can be a strategic approach to fostering a generation with character and integrity.